Clinical Insights into Homeopathic Management of Onychomycosis (Homoeopathy for All, 2024)
Onychomycosis traditionally  referred to a non dermatophytic  infection of the nail but is now  used as a general term to denote  any fungal nail infection (Tinea  unguium specifically describes a  dermatophytic invasion of the nail  plate)., Onychomycosis is the most  prevalent nail disorder, affecting  more than 50% of all nail diseases,  and is characterized by fungal  infections caused by dermatophytes,  yeasts, and non-dermatophyte fungi.  This condition typically manifests  as discoloration, thickening, and  separation of the nail from the  nail bed, leading to both aesthetic  concerns and potential discomfort.
Keywords: targeting; conventional treatments; Onychomycosis